Progressive collapse of a steel structure under expected snow loads - Alemdar, Zeynep Firat; Alemdar, Fatih (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
The structural design process has many vital roles in preventing the collapse of structures and should be conducted according to national obligatory standards. However; structural failures or even catastrophic collapses based on improper design, underestimated design loads, unexpected extreme loads, and improper erection are reported worldwide on large-span structures. A steel structure of the factory partially collapsed under expected snow loads in the western part of Turkey was investigated in this study. The possible reasons for the collapse of the system were examined by visual inspections and analytical results. The load-carrying capacities of the main girders and purlins were determined using the buckling analyses of the structural member. The nonlinear geometric analysis of the entire steel structural system was defined to evaluate the vertical load-carrying capacity of the main girder. The progressive collapse mechanism of the system was determined. The obtained results indicate that the snow load is not the main reason for the collapse and mistakes in the project design, constructional defects and inadequate capacity of structural elements are the primary reasons behind the collapse.
Keywords: Progressive collapse; Steel structure; Structural deficiency; Buckling analysis; Snow; ROOF; Engineering; Materials Science